Spatial Autocorrelation of Dengue and Its Relationship with Population Density in South Kalimantan, Indonesia - Norjanah, Norjanah; Ridha, Muhammad Rasyid (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Dengue is a viral infection transmitted to humans through the bite of Aedes aegypti and Ae. Albopictus mosquitoes. Demographic factors that may influence the development and prevalence of dengue cases include variations in population density, community characteristics, and economic and social demographics. This study aimed to determine the distribution, spatial autocorrelation, and relationship between population density and dengue.Methods: Secondary data analysis was conducted in Hulu Sungai Selatan District, South Kalimantan, Indonesia. Data on dengue cases, population density for each sub-district, and base maps were collected to and then be used as analysis material. Spatial autocorrelation was analyzed using the Moran's index and Local Spatial Autocorrelation Index (LISA), then the correlation of population density with dengue was carried out using linear regression.Result: Spatial Autocorrelation had positive autocorrelation and clustered spatial patterns in 2017 and 2018; whereas in 2019-2021 was negative and the spatial pattern was spread. There was a decrease in cases from high to low (HL) in Kandangan District in 2021, which was previously high to high (HH) in 2017-2019. There was a correlation between population density and dengue (R-value=0.448) with a moderate category.Conclusion: Dengue cases are more widespread in Kandangan. The spatial autocorrelation of dengue that occurs between sub-districts in Hulu Sunga Selatan District is due to sub-district location in the city center. There is a correlation between dengue and population density. Therefore, controlling dengue should be prioritized in the city center area first to break the chain of dengue transmission between sub-district in Hulu Sunga Selatan District.